RESPONSE YIELD OF TWO PROMISING CHICKPEA GENOTYPES TO DIFFERENT PHOSPHORUS LEVELS - HUSSAIN, MOHEMMED ALI; ELYAS, JALAL ABDULLAH; SADIQ, ESMAT MUSTAFA; HASAN, BARAVAN HUSSEIN (Journal of Duhok University, 2023)
The experiment was conducted to investigate the effect of two promising chickpea genotypes at different phosphorus levels (0,23,46 and 69kgha-1P2O5) at research station of Agricultural Research center. The experiment units were laid out in factorial experiment using randomize complete block design with three replications. The results indicated that asignificant effected the chickpea genotypes,phosphorus levels and their interaction on plant height, first podheight, number of nodules per plant ,number of main and secondary branches per plant, number of pods per plant,100 seed weight and seed yield. Also the result revealed that the Flip07-245C gave the highest seed yield 449.3g at 69kg ha-1P2O5,while the lowest value (157.7g) at rate 0 phosphorus application was recorded by FLipo7-223, allfertilizerP2O5levels gave highest grain yield than thecontrol. All traits was correlated asignificant and positive correlated with yield with plant height (0.906), first pod height (0.877) and 0.935 with 100 seed weight. From the results of the study it was concluded that the application of 69kg ha-1P2O5had result better performance in all of the phosphorus levels applied and FLipo7-245Cchikpea genotyperesponded better with regard to grain yield